Kajian tentang Pengaruh Pelatihan, Peralatan dan Kegiatan Pemasaran terhadap Hasil Tangkapan serta Pendapatan Kelompok Nelayan di PPN Pekalongan - Suprihono Setyawan; Muhammad Syaqiq; Ageng Prasetyo (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2025)
This study aims to investigate the impact of training, equipment availability, and marketing activities on the catch and income of fishermen who are members of fishing groups in the Pekalongan Nusantara Fisheries Port (PPN) area. The research activity involved fishing groups, with respondents selected randomly and balanced proportions, resulting in 80 fishing groups. The method used was a quantitative approach. However, among all respondents, only 30 fishing groups were willing to complete the questionnaire. The main objective of this study was to identify factors that influence fishermen's catch and income, and to determine the most dominant factor. The results of the analysis showed that the first hypothesis (H1) had a coefficient of 9.687 with a significance level of 0.000, indicating that it was accepted. The second hypothesis (H2) had a coefficient value of 0.165, with a significance level of 0.703, and was therefore rejected. Meanwhile, the third hypothesis (H3) showed a coefficient value of -0.063 with a significance level of 0.027. Based on the regression test, the relationship between variables is classified as low with an R value of 0.315. The independent variable influences the dependent variable by 0.236, or 23.6%, while factors outside the scope of this study influence the remaining 76.4%. The recommendation is for the local government to encourage the development of the fisheries sector as a strategic sector, while also evaluating whether this sector is worthy of being the mainstay of the economy for fishermen, especially in the Pekalongan PPN area.